KAJIAN TEORITIS GLAUKOMA: DASAR TEORITIS UNTUK PENDEKATAN DIAGNOSTIK DAN TERAPI - Mutiara Anissa; Birman, Yuliza; Naima Lassie (Nusantara Hasana Journal, 2025)
Glaucoma is a group of chronic eye diseases characterized by optic nerve damage and increased intraocular pressure (IOP), and is the second leading cause of blindness in the world after cataracts. This article aims to review the basic theories of glaucoma including definition, epidemiology, classification, pathophysiology, clinical manifestations, diagnosis, management, complications, and prognosis. The main management involves IOP-lowering therapy, either medication through eye drops or surgical interventions such as trabeculectomy. Early detection and adherence to therapy are very important in preventing disease progression and reducing the risk of blindness. This review provides a comprehensive theoretical understanding as a basis for optimal glaucoma management.